Proceedings of the 2019 4th International Conference on Modern Management, Education Technology and Social Science (MMETSS 2019 2019
DOI: 10.2991/mmetss-19.2019.82
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Content Features of Short Video Marketing on Consumer purchase intentions

Abstract: The short video industry is in the hotspot which favored by more and more users and advertisers. The length of short video is usually less than 5 minutes. The content is refined and rich, adapting to the fast-paced life, and the mode of vertical screen is also in line with the habits of mobile users. The interaction is more active, and the maturity of artificial intelligence technologies such as face recognition makes short videos more interesting and entertaining. The rapid development of short videos gives r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 1 publication
0
25
0
5
Order By: Relevance
“…To compare: consumers having the brand awareness orientation perceive the brand as a symbol of credibility and prestige, whereas those with value awareness usually check and compare the prices and quality of different brands through social media to ensure a best-value purchase [11]. To this end, many companies employ social media in carrying out low-cost and high-efficiency marketing activities for consumers [7,12]. Social media is a marketing tool wielded for four primary purposes: market research and feedback; brand promotion and reputation management; customer service and customer relationship management; and business network [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To compare: consumers having the brand awareness orientation perceive the brand as a symbol of credibility and prestige, whereas those with value awareness usually check and compare the prices and quality of different brands through social media to ensure a best-value purchase [11]. To this end, many companies employ social media in carrying out low-cost and high-efficiency marketing activities for consumers [7,12]. Social media is a marketing tool wielded for four primary purposes: market research and feedback; brand promotion and reputation management; customer service and customer relationship management; and business network [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The short-term increase in openness to seeking treatment, which our follow-up data show can be repeated, creates a timelimited window of opportunity to connect essential workers with mental health services. Short video marketing research 32 shows that video platforms that introduce an actionable function to focus the desired intention change (e.g. a linkable shopping cart on commercial advertisements) have significantly increased efficacy compared with identical videos lacking this function.…”
Section: Discussionmentioning
confidence: 99%
“…According to Autio (2020), when a young adult recognises a need that must be met, he or she seeks for information on the thing that will be purchased. As Xiao et al (2019) acknowledge, those short videos can help them understand and evaluate products in the process of purchasing decisions without exerting much effort. The results also showed that the products in the TikToker short videos drew the attention of the majority of the respondents.…”
Section: Findings and Discussionmentioning
confidence: 99%